Unexpected landscape-scale contemporary gene flow and fine-scale genetic diversity in rural hedgehogs - Hongli Yu; Lauren J. Moore; Axel Barlow; Louise K. Gentle; Deborah A. Dawson; Gavin J. Horsburgh; Lucy Knowles; Philip J. Baker; Adam Bates; Helen Hicks; Silviu Petrovan; Sarah Perkins; et al. (Conservation Genetics, 2025)
Agricultural intensification is one of the major forces driving populations of many traditionally common native species into smaller, fragmented populations which are prone to isolation and loss of genetic diversity. Identifying the spatial extent and characteristics of rural systems that support gene flow and promote genetic diversity for these species is thus essential for their long-term conservation. Here we used asymmetric autosomal genetic structure between sexes to investigate current gene flow among four neighbouring suburban populations of hedgehogs ( Erinaceus europaeus ) in England, which are separated by agricultural land. Contrary to expectations, we found that individuals belonged to a single genetic population despite the populations being separated by unoccupied agricultural land. Spatial autocorrelation was significant in adult female hedgehogs, but non-significant in adult males, revealing male driven contemporary gene flow between local populations. The results suggest that male hedgehogs are capable of moving between population patches separated by at least 3 km across the agricultural matrix. This finding is crucial to aid the development of a conservation strategy for hedgehogs as, for the first time, it shows the extent that previously assumed isolated populations across a perceived inhospitable landscape are connected by current gene flow. Higher within patch relatedness, and lower allelic richness were found from smaller suburban patches, largely reflecting local population size, indicating an early stage of genetic diversity loss due to habitat loss and associated fragmentation. Our study illustrates that considering current gene flow and local genetic diversity together is important to better understand habitat effects on genetic variation and to inform future conservation management.